Potensi Simpanan Karbon di Hutan Kota Pulau Bungin, Teluk Kuantan, Kabupaten Kuantan Singingi, Provinsi Riau - Ewi Irfani; Rini Dwi Putri; Pebriandi Pebriandi; Sonia Somadona (MAKILA, 2026)
Bungin Island City Forest located in Teluk Kuantan, Kuantan Singingi Regency, Riau Province with an area of 3.7 ha is one of the Green Open Spaces (RTH) that has the potential to store carbon. This study aims to determine the carbon storage potential stored in vegetation and soil in the Bungin Island Urban Forest area. The research method involved making plots measuring 20 m x 100 m with a sampling intensity (IS) of 30%, using the systematic with random star method. Data collection included measurement of tree diameter (DBH), identification of plant species, wood specific gravity, and analysis of biomass and carbon storage from five constituent components, namely: (1) aboveground biomass (seedlings, understory, saplings, poles, and trees), (2) belowground biomass (roots), (3) necromass (dead trees), (4) litter, and (5) soil. Estimating carbon stocks using biomass data. Allometric equations were used to assess aboveground plant biomass. Data analysis for other carbon sources uses formulas according to national standards (SNI 7724: 2019). The results showed that the total carbon storage in Bungin Island Urban Forest was 155.32 tons/ha, consisting of aboveground carbon storage of 94.92 tons/ha (61.11%), subsurface carbon storage of 35.12 tons/ha (22.61%), litter carbon storage of 0.36 tons/ha (0.23%), necromass storage of 0.49 tons/ha (0.32%), and soil carbon storage of 24.43 tons/ha (15.73%).